Conceptual basis of economic and business culture of PRC (Journal of Oriental Studies, 2018)
This article covers the concept of business culture and analyzes the peculiarities of China’s economic  and business culture. The authors have analyzed the relationship between Chinese traditional cultureand modern Chinese economic and business culture. The influence of Chinese CNPC traditional cultureon the Chinese business culture has been studied.